PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN GITAR YAMAHA DI JAKARTA TIMUR - Nurul Setyawati; Iwan Kurniawan Subagja (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
This research aims to test and determine the influence of product quality and price on purchasing decisions for Yamaha guitar products simultaneously and partially. The research was conducted on consumers who bought Yamaha products in East Jakarta. The sampling technique used purposive sampling and data analysis used multiple and simple linear regression analysis. The results of the research showed that product quality and price had a positive and significant effect both simultaneously and partially on purchasing decision.